ANALYSIS OF THE DEFORMATION SURFACE EVOLUTION WITH ALLOY D16AT COMPRESSION AND TENSION - Маслак, Т. П. (Science-based technologies, 2013)
It has been conducted the investigation for the comparing the features of deformation relief evolution under tension and compression. It includes computer-aided optical monitor, X-ray diffraction analysis of microstress in the surface layer and electron microscope investigation of surface morphology. It has been shown the insensitivity of accumulated fatigue damage of alclad aluminum alloy D16AT at the initial stage of fatigue, which are defined by deformation relief, is not depended of sign stress.